246 PENGARUH EDUKASI KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN SISWA TENTANG TRIAD KRR (SEKSUALITAS, HIV/AIDS, DAN NAPZA) DI SMK SWADAYA KOTA SEMARANG TRI WULAN II TAHUN 2017 - Permai Jusnita Sihite; Djoko Nugroho; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
In 2012 some cities data,records about 21-30% of teenagers have had premarital sexual intercourse. The purpose of this research is to analyze the effect of Triad KRR (sexuality, HIV / AIDS and NAPZA) using the lecture and brainstorming method on the level of knowledge of adolescents in SMK Swadaya Semarang. This research uses experimental research method (true experimental) with randomized design group (RDG). The population of this study is the students of class XII is 107 students. Sampling using simple randomized randomization are 96 students with RAK (Group Random Design) design of 6 groups and each group there are 16 students. Data were analyzed by univariate and bivariate analysis with two way anova test. The results showed that there was an effect of reproductive health education using Triad KRR material (Sexuality, HIV / AIDS and Drugs) to the students' knowledge (p = 0.0001). There is influence of reproduction health education with lecture and brainstorming method (0.0001). The highest post-test score of sexuality material with lecture method (13,25), material of HIV / ADIS by using caramah method (17,12%) while drug substance with lecture method (14,25%). The school should establish PIK KRR (Center for Information and Counseling of Reproductive Health of Adolescents) to further improve students' knowledge about reproductive health related Triad KRR (sexuality, HIV / AIDS and drug) using lecture method.